Trajectory, drivers, and reduction of greenhouse gas emissions from urban water system in China during 1980–2030 - Shiyu Pei; Zonghan Li; Yi Liu; Chunyan Wang; Hao Wu; Shuming Liu; Yujun Huang (Resources, Environment and Sustainability)
Urban water systems (UWSs) continuously evolve in response to changes in urban populations, technological advancements, and lifestyle shifts, resulting in significant changes in greenhouse gas (GHG) emissions. Understanding how GHG emissions vary across the different developmental stages of a UWS is crucial for charting pathways toward carbon neutrality under varying levels of urbanization and infrastructure maturity. To explore the long-term patterns of GHG emissions from the UWS, we developed a systematic accounting framework encompassing four energy-related subsystems: water extraction, water supply, residential water use, and wastewater treatment. We applied this framework to China’s UWS across its transitional trajectory—from early development to system-wide maturity (1980–2020) at the provincial level. Results show that over the 40 years, GHG emissions from China’s UWS increased approximately 14-fold, surpassing the overall rate of population growth by 143.9%. From the early 1990s till now, residential water use emerged as the dominant source of UWS-related emissions, accounting for approximately 77.6% of total emissions. Our scenario analysis estimates a potential 34.0% reduction in China’s carbon emissions (128.3 Mt CO2-eq) by 2030 through water-saving strategies. This study offers critical insights into promoting low-carbon operations and sustainable management of UWS, and serves as an important reference for global efforts net-zero water infrastructure.